Analisis Muatan Nilai-Nilai Pendidikan Karakter Pada Buku Teks IPS SMP Kelas VII Kurikulum 2013 dan Implementasinya di SMP Negeri 1 Lembang - Khoirunnisa, Ayu; S, Sapriya; Rakhman, Muhammad Arief (Jurnal Ilmiah Wahana Pendidikan, 2023)
Character education is one of the educational programs that can develop the positive character of students and overcome juvenile delinquency that occurs. One of the cultivation of character education in the school environment is through textbooks as the main learning resource. The purpose of this research is to find out what character education values are contained in the Junior High School Social Studies Textbook Grade VII Curriculum 2013 Revised Edition 2017. This study used a qualitative research approach with a narrative content analysis method with data collection techniques of interviews with one of the junior high school teachers, classroom observation to find out the implementation of character values at SMP Negeri 1 Lembang, documentation study of lesson plans, and analysis of textbook content. The results of the study showed that the Junior High School Social Studies Textbook Grade VII Curriculum 2013 Revised Edition 2017 contains 18 character education values. These values are included in the learning materials, individual activities, group activities, and reflect features. However, there are other values that are equally important in relation to juvenile delinquency. Group activity as one of the most impactful activities on the internalization process that contains three aspects at once. Character values appear more during implementation than those contained in textbooks and lesson plans.